Socially responsible investing: does the social pillar of firms´ ESG factors provide information for investors- portfolio returns? Evidence from Europe - Jaeger, Moritz Nikolaus (2021)
Using a large dataset of social ratings, this empirical analysis examines the financial performance of portfolios based on socially responsible investments in European equities. While there remains a dissensus among academics whether socially responsible investments can yield a significant outperformance, this thesis provides evidence that socially driven investments can provide positive and statistically significant risk-adjusted returns to the investor. Portfolios are for med through the best-in-class/ worst-in-class approach, using social ratings cores and sub-scores. Portfolio performance is evaluated in a Fama-French-Carhart four-factor model, providing evidence for positive and significant alphas within several long-only as well as net-zero investment portfolios (long-short).